The Digital Framing as an Unlawful Act in the Dispute Between Yai Min and Sahara - Irene Puteri A. S. Sinaga; Abigail Angeline Yap; Sandriani Garanta; Valonia Nevada (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This research analyzes the application of the elements of unlawful acts (Perbuatan melawan hukum or PMH) in defamation disputes arising from digital media under Indonesian civil law, using the case between Imam Muslimin (Yai Min) and Nurul Sahara as a contextual reference. In contrast to previous studies, this research provides an integrative perspective that bridges criminal and civil approaches to defamation, aiming to demonstrate how the elements of unlawful acts, namely fault, loss, causal relationship, and violation of rights are applied in assessing online defamation within the framework of civil liability. This study employs a normative legal research method with a case approach as the primary analytical framework. The analysis focuses on the implementation of Article 1365 of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata or KUH Perdata) concerning unlawful acts, in conjunction with relevant provisions of the Electronic Information and Transactions Law (ITE Law). The sources of legal materials consist of primary materials (statutory regulations), secondary materials (legal doctrines, journals, and scholarly articles), and tertiary materials (credible media reports and supporting information). Data are collected through library research and analyzed qualitatively to evaluate the coherence between positive legal norms and their practical application in the Yai Min–Sahara case. The findings indicate that Sahara’s actions satisfy the elements of an unlawful act, particularly in the form of defamation, thereby highlighting the importance of responsible digital behavior and strengthening legal awareness regarding online communication ethics and liability.